Peran Diklat Dalam Meningkatkan Profesionalitas Guru - Arya Bisma Nugraha; Sasmi Nelwati (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Training and education (diklat) play a significant role in enhancing the professionalism of teachers. In an ever-evolving educational landscape, teachers are required to possess competencies that extend beyond mere mastery of content; they must also demonstrate pedagogical and managerial skills. Through training programs, teachers can access various workshops designed to enrich their knowledge and skills, including innovative teaching methods, the use of technology in learning, and effective assessment strategies. Training also serves as a platform for sharing experiences and best practices among teachers, fostering a supportive learning community. By participating in regular training, teachers can update their knowledge in line with curriculum developments and student needs. Furthermore, training contributes to increased motivation and job satisfaction among teachers, positively impacting their performance in the classroom. Overall, training is a crucial investment in the professional development of teachers, ultimately contributing to the improvement of educational quality and student learning outcomes. Therefore, the role of training in enhancing teacher professionalism cannot be overlooked and should be prioritized in educational policy.